PEMAHAMAN SISWA SMA TENTANG MATERI LIMIT - Haminah, Nur Haminah; Rahmat Udani (Jurnal Matematika dan Sains (JMS), 2024)
This study uses a qualitative descriptive method that aims to be able to analyze high school students' understanding of limits, especially grade 12, the analysis uses a limited sample where the subject has been determined because the subject has learned limits in grade 11, therefore it is made a research subject, research is conducted online using google form, where 7 research subjects were taken, namely 7 students from MAN 1 Sijunjung, Sijunjung district, West Sumatra, namely through several tests, namely 7 multiple choice questions and questions regarding the extent of students' understanding of limits and after seeing that some 12th grade students had understand the limits of algebraic functions and some of them still don't understand the limits of the material limits of trigonometry functions where there are many difficulties when you have to use the torema where if you want to use it you have to memorize the theorem before working on the given problem.